GRAMMATICAL AND LEXICAL ANALYSIS IN OPRAH WINFREY TALKSHOW - Ratna Sari Dewi; Mashud Ramadhani (VISION, 2022)
This study deal with the analysis grammatical and lexical in talkshow Oprah Winfrey. The objectives of the study were not only to find out the grammatical and lexical meaning, but also to describe how the host used grammatical and lexical in talkshow Oprah Winfrey. The data in this research were taken from talkshow Oprah Winfrey. This research used a descriptive qualitative method. In doing this research, the data were analyzed using library research. The source of data in this study was utterances taken from video talk show of Oprah Winfrey that entitled Peter Walsh’s stripped Down Family Challenge, which downloaded from Youtube. The data focused on the utterances of the guest and host in talkshow Oprah Winfrey that consist of Grammatical and Lexical Meaning. From the data obtained, there were one hundred and six (106) utterances found in talkshow Oprah Winfrey. It was found 2 types of Semantic in this research, there were 63 utterances of Grammatical meaning and 43 utterances of Lexical meaning. To analyze the data, the researcher used the theory proposed by Miles & Huberman (2014) to know the grammatical and lexical meaning.